Comparison of immunotherapy based total neoadjuvant therapy or standard neoadjuvant chemoradiation for locally advanced rectal cancer: a multi-institutional retrospective study - Zhao, Wen; Gao, Wenxing; Du, Jitao; Li, Dingchang; Liu, Xianqiang; Chang, Zhengyao; Chen, Peng; Sun, Xu; Zhao, Yingjie; Jiao, Hanqing; Wan, Xiangbin; Dong, Guanglong (Frontiers in Immunology, 2025)
BackgroundCombining radiation therapy with immunotherapy produces a synergistic effect in patients with microsatellite stable/mismatch repair-proficient (MSS/pMMR) locally advanced rectal cancer (LARC). This study aimed to evaluate the long-term outcomes and safety of immunotherapy combined with long-course chemoradiotherapy (ICIs + nCRT) versus immunotherapy combined with total neoadjuvant therapy (ICIs + TNT).MethodsThis retrospective study collected clinical data of adult patients with clinical T3-4 and/or N1 rectal adenocarcinoma who underwent ICIs + TNT or ICIs + nCRT followed by curative surgery at four medical centers between March 2020 and August 2021. The study compared clinical efficacy, disease-free survival (DFS), overall survival (OS) at 3 years postoperatively, and adverse event.ResultsAmong 211 enrolled patients, 89 (42%) received ICIs + TNT, while 122 (58%) underwent ICIs + nCRT, with a median age of 56.0 years (range, 20.0-75.0 years). The ICIs + TNT group had a higher median number of resected lymph nodes (15.0 [range, 4.0-37.0] vs. 13.0 [range, 3.0-33.0], P=0.028) compared to the ICIs+nCRT group. However, the groups had no substantial difference in median operative time. The pathological complete response (pCR) rate was 49.4% (44/89, 95% confidence interval [CI] 39.8%-61.3%) in the ICIs + TNT group compared to 35.3% (43/122, 95% CI 26.8%-44.4%) in the ICIs + nCRT group, respectively, with significant difference (P=0.039). After adjusting for potential confounders, the 3-year DFS rates were comparable between the two groups (84.3% vs. 81.9%; P=0.620), as were the OS rates (94.0% vs. 91.1%; P=0.634). Factors independently associated with poorer DFS included age ≤50 years (P=0.044) and a neoadjuvant rectal (NAR) score ≥8 (P=0.008). Similarly, patients aged ≤50 years (P=0.025) exhibited a trend toward worse OS than those older than 50 years. The safety profiles of the two treatment groups were similar.ConclusionsOverall, ICIs + TNT demonstrated therapeutic efficacy and a safety profile comparable to ICIs + nCRT in patients with LARC and MSS/pMMR status. Although ICIs + TNT achieved numerically higher downstaging rates, it was not associated with improved survival outcomes. These findings underscore the importance of refining patient selection criteria and making judicious treatment decisions to enhance the prognosis of individuals with rectal cancer.